2010
DOI: 10.1002/bdd.720
|View full text |Cite
|
Sign up to set email alerts
|

Acyl glucuronides: the good, the bad and the ugly

Abstract: Acyl glucuronidation is the major metabolic conjugation reaction of most carboxylic acid drugs in mammals. The physiological consequences of this biotransformation have been investigated incompletely but include effects on drug metabolism, protein binding, distribution and clearance that impact upon pharmacological and toxicological outcomes. In marked contrast, the exceptional but widely disparate chemical reactivity of acyl glucuronides has attracted far greater attention. Specifically, the complex transacyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(151 citation statements)
references
References 183 publications
3
145
0
Order By: Relevance
“…3; Table 6), two nonsteroidal anti-inflammatory drugs that are commonly administered both topically and orally. Because acyl glucuronides may be chemically reactive (Regan et al, 2010;Boelsterli and Ramirez-Alcantara, 2011;Dickinson, 2011), this finding has potential implications for skin toxicity, such as skin rash, an adverse effect observed for numerous therapeutic drugs (Mayorga et al, 2009;Chanprapaph et al, 2014). A more recent study also reported that the formation of 12-hydroxynevirapine sulfate induced skin rash in rats (Sharma et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…3; Table 6), two nonsteroidal anti-inflammatory drugs that are commonly administered both topically and orally. Because acyl glucuronides may be chemically reactive (Regan et al, 2010;Boelsterli and Ramirez-Alcantara, 2011;Dickinson, 2011), this finding has potential implications for skin toxicity, such as skin rash, an adverse effect observed for numerous therapeutic drugs (Mayorga et al, 2009;Chanprapaph et al, 2014). A more recent study also reported that the formation of 12-hydroxynevirapine sulfate induced skin rash in rats (Sharma et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Acyl glucuronides, which are enzymatic products formed by glucuronidation of carboxylic acids (Stachulski et al, 2006), are capable of undergoing the following: 1) hydrolysis to parent aglycone mediated by b-glucuronidases, nonspecific esterases, hydroxyl ion, or serum albumin; 2) intramolecular acyl migration to form positional isomers that are resistant to b-glucuronidase-mediated hydrolysis; and 3) covalent binding to proteins via transacylation or glycation mechanisms (Regan et al, 2010). Acyl glucuronides, however, differ widely in their chemical reactivity, which is attributed to the chemical structure of the aglycone moiety (Stachulski et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…N-glucuronides (primary, secondary and N-hydroxylated amines) are hydrolyzed under mild acidic conditions but quartenary ammonium glucuronides under basic conditions [25]. Additionally, enzymatic hydrolysis of acyl glucuronides may be hindered due to acyl migration what leads to ß-glucuronidase resistant derivates [59]. Nevertheless, if the ß-glucuronidase treatment is successful for the metabolite of interest, this procedure should be the method of choice.…”
Section: Indirect Quantificationmentioning
confidence: 99%
“…Different acyl glucuronides have been shown to have different rates of hydrolysis. However, mildly acidic conditions (pH 3-5) should be the most desirable pH for minimizing the reaction in biological samples [59,111]. Acyl glucuronides (1-O-acyl glucuronides) are also susceptible to internal migration under both, physiological and alkaline conditions.…”
Section: Metabolite Stabilitymentioning
confidence: 99%